2015
DOI: 10.1021/acscatal.5b02106
|View full text |Cite
|
Sign up to set email alerts
|

Phosphanyl Methanimine (PCN) Ligands for the Selective Trimerization/Tetramerization of Ethylene with Chromium

Abstract: . (2015) This document is the Accepted Manuscript version of a Published Work that appeared in nal form in ACS Catalysis, copyright c American Chemical Society after peer review and technical editing by the publisher. To access the nal edited and published work see http://dx.doi.org/10.1021/acscatal.5b02106. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…However, too much ligand steric bulk could impede ethylene coordination to the catalyst. The correlation between catalytic activity and PE formation is also reflected in publications involving other bidentate ligand motifs as well as with tridentate ligands …”
Section: Resultsmentioning
confidence: 86%
“…However, too much ligand steric bulk could impede ethylene coordination to the catalyst. The correlation between catalytic activity and PE formation is also reflected in publications involving other bidentate ligand motifs as well as with tridentate ligands …”
Section: Resultsmentioning
confidence: 86%
“…7,8 Several chromium complexes have been reported that oligomerise ethylene with high selectivity to 1-hexene or 1-octene, for example those based on PNP ligands, [9][10][11][12] and more recently with PNC=N and PC=N ligand systems. 13,14 The trimerisation of ethylene to 1-hexene with a pyrrole/chromium-based catalyst is operated by the Phillips Petroleum Company, 15 and Sasol has recently commercialised a tri/tetramerisation technology based on PNP/chromium catalysts for the production of 1-hexene and 1-octene. 16 Some examples of commercial oligomerisation catalysts are collected in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, Cr(III) complexes coordinated by the diphosphinothiophenes 59a -59e ( Figure 21 Cr(acac)3 formed precatalysts that displayed TOFs of between 126900 and 312500 h -1 for ethylene oligomerization with 61c producing 1-hexene and 1-octene in a 2:1 ratio along with some polymer. The 1-phosphanyl methanimine P^N-ligands, 62a -62h ( Figure 21) have also emerged as compatible supports for chromium ethylene tri-/tetramerization catalysts [146] as have the phosphazane ligands 63a -63e ( Figure 21) [147]. For example, the chromium catalyst derived from N-cyclohexyl-containing 63e displayed a high activity of 316.7 kg (g Cr) −1 h −1 along with a high total selectivity of 85.1% towards 1hexene (45.7%) and 1-octene (39.4%).…”
Section: Bi-and Tridentate Ligands Based On P-and S-donors and Their mentioning
confidence: 99%
“…While homogeneous chromium catalysts have shown their importance in oligomerization and polymerization of ethylene (see section 2), they have also emerged as effective catalysts for the selective trimerization and more recently tetramerization of ethylene. Moreover, the products, 1-hexene and 1octene are in high demand due to their use as comonomers for the production of linear low-density polyethylene (LLDPE) [38,40,48,81,[131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147]. In this section, we again use the type of multidentate ligand to divide the sections with catalysts based on N^N^N discussed first before moving on to P^P, S^P^S, S^N^S, P^N^P and P^P^O systems.…”
Section: Chromium Catalysts For Selective Ethylene Trimerization and mentioning
confidence: 99%